Acanthamoeba: An Overview of the Challenges to the Development of a Consensus Methodology of Disinfection Efficacy Testing for Contact Lens Care Products. Issue 6 (November 2018) - Brocious, Jeffrey; Tarver, Michelle E.; Hampton, Denise; Eydelman, Malvina
Abstract : Abstract: With the increasing incidence of more pathogens that can cause microbial keratitis (MK), it is necessary to periodically reassess disinfection multipurpose solutions testing requirements to ensure that relevant organisms to challenge them are being used. Current testing protocols have included common pathogens such as Pseudomonas aeruginosa, Staphylococcus aureus, Serratia marcescens, Candida albicans, and Fusarium solani but have omitted less common pathogens such as Acanthamoeba . Specifically, Acanthamoeba sp. has recently been identified as a prevalent cause of MK in certain countries. Developing an appropriate protocol for this unique organism presents a challenge, given its two distinct life stages, methods to grow the organism, encystment techniques, and many other parameters that can affect testing outcomes. Therefore, the appropriate combination of these parameters is crucial to developing a protocol that ensures consistent, accurate results. The FDA has recognized the importance of establishing a standardized testing protocol for this pathogen and embarked on research efforts to provide a recommended testing protocol for testing contact lens care products.